2001
DOI: 10.1093/jnci/93.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Hypoxia-Inducible Factor-1  During Breast Carcinogenesis

Abstract: The level of HIF-1 alpha increases as the pathologic stage increases and is higher in poorly differentiated lesions than in the corresponding type of well-differentiated lesions. Increased levels of HIF-1 alpha are associated with increased proliferation and increased expression of ER and VEGF. Thus, increased levels of HIF-1 alpha are potentially associated with more aggressive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
439
4
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 555 publications
(484 citation statements)
references
References 41 publications
33
439
4
8
Order By: Relevance
“…It has been shown that high microvessel density, VEGF overexpression, and increased lactate production are associated with a poor prognosis in human malignancies. 13,14,36 Similar to the results from our previous study, 19 we found that high levels of HIF-1␣ were correlated with overexpression of VEGF, one of its main downstream effectors, confirming angiogenesis as one of the proposed mechanisms by which HIF-1 activation stimulates tumor growth and metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It has been shown that high microvessel density, VEGF overexpression, and increased lactate production are associated with a poor prognosis in human malignancies. 13,14,36 Similar to the results from our previous study, 19 we found that high levels of HIF-1␣ were correlated with overexpression of VEGF, one of its main downstream effectors, confirming angiogenesis as one of the proposed mechanisms by which HIF-1 activation stimulates tumor growth and metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…No studies measuring O 2 tension in breast carcinoma in relation to patient survival have been published; however, in patients with cervical carcinoma, it is known that in vivo intratumoral hypoxia predicts poor survival. 1 In the current study and in our previous report, 19 HIF-1␣ staining often was observed in viable cells surrounding areas of necrosis, suggesting that hypoxia contributes to HIF-1␣ up-regulation in breast carcinoma. Adaptation to hypoxia is mediated by HIF-1, which stimulates angiogenesis (through VEGF) and high and anaerobic metabolism (through glucose transporters and glycolytic enzymes).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations